Improvement of cutting performance of carbide cutting tools in milling of the Inconel 718 superalloy using multilayer nanocomposite hard coating and cryogenic heat treatment - Kurşuncu, Bilal; Caliskan, Halil; Guven, Sevki Yilmaz; Panjan, Peter; Kurşuncu, Bilal (Springer London Ltd, 2018)
In this study, milling of the Inconel 718 superalloy was performed in dry conditions with the aim of reducing the adverse effects of the coolant on the environment. As is known, cutting tools quickly complete their life due to the high-temperature on the cutting zone in the dry condition milling process of hard materials. The nanocomposite TiAlSiN/TiSiN/TiAlN thin film was deposited on the cutting tools and then subjected to cryogenic heat treatment to increase the tool life of the used cutting tools. As a result, the life of the cutting tools has been increased by the thin film coating and cryogenic heat treatment applied to the cutting tools. After cryogenic treatment at a cutting speed of 30 m/min, the tool life of uncoated, TiN-, nanocomposite TiAlSiN/TiSiN/TiAlN-, and TiAlN-coated carbide cutting tools increases by 54, 110, 29, and 30%. The applied cryogenic heat treatment resulted in an 18% increase in the hard eta phase of the structure of the carbide cutting tools. In addition, cryogenic heat treatment improved the adhesion of hard coatings to the substrate. The EDS analysis applied to the worn tools revealed that the mechanisms causing wear of the cutting tools were abrasion and adhesion.
Keywords: Inconel 718; Carbide Cutting Tool; Hardmilling; Cryogenic Heat Treatment; Nanocomposite Hard Coatings